Artificial Intelligence and Criminal Liability: A Preliminary Study within the Indonesian Legal System - Hutapea, Novelina Mutiara Sariati; Sitepu, Desy Kartika Caronina; Damanik, Jenriswandi; Sianipar, Srikandi Karmeli Lusia (Jurnal Ilmu Hukum Kyadiren, 2026)
The rapid development of Artificial Intelligence (AI) presents significant challenges for Indonesian criminal law, particularly in determining accountability for actions involving AI, whether as an auxiliary tool or as an indirect perpetrator. This study seeks to examine the current criminal law framework, identify deficiencies in the Criminal Code (KUHP), the Electronic Information and Transactions Law (ITE Law), and related regulations, and assess the applicability of alternative liability models, including vicarious liability and strict liability. Employing a normative juridical approach—through the analysis of statutory provisions, legal doctrine, and international case studies—this research finds that national regulations remain predominantly reactive, fail to adequately anticipate the emergence of autonomous AI, and encounter technical evidentiary challenges arising from the ‘black box’ phenomenon. The findings suggest that alternative liability models are better suited to the distinctive characteristics of AI. The study concludes that a responsive reformulation of criminal law norms is essential to ensure legal certainty, protect victims, and facilitate effective law enforcement in the context of AI.